HUMAN RESOURCE MANAGEMENT STRATEGY IN IMPROVING THE PROFESSIONAL COMPETENCE OF PRODUCTIVE TEACHERS AT VOCATIONAL HIGH SCHOOLS (SMK) IN SANGATTA (Pena Cendekia Insani, 2026)
The purpose of this study is to describe and analyze human resource management, especially in improving the competence of productive teachers in vocational schools in Sangatta. This study uses a descriptive qualitative method including planning, organizing, implementing, supervising, and management models. Data collection was carried out using interview, observation, and documentation methods. Data analysis techniques refer to the concept of Miles and Huberman. The results of the study indicate that human resource management in improving the professional competence of productive teachers has been implemented systematically and continuously through the functions of planning, organizing, implementing, and supervising. In the planning stage, the school developed a program for developing the competence of productive teachers based on the school's vision and mission, needs analysis, and the involvement of the business world and industry. Organization is carried out through the preparation of an organizational structure, division of tasks, collaboration, and mentoring among productive teachers. Implementation is carried out through internal and external training, industrial internships, professional certification, and dissemination of training results. Supervision is carried out systematically through academic supervision, learning observations, teacher performance evaluations, analysis of student learning outcomes, feedback, and graduate absorption. Overall, the human resource management model applied is the model according to Hunger and Wheelen. This model is needs-based, collaborative, and industry-oriented, and is supported by effective principal leadership and the environment, thus contributing positively to improving the professional competence of productive teachers and the quality of learning and becoming a reference for other schools in improving the professional competence of productive teachers at Vocational High Schools in Sangatta.